Notoginsenoside R1 (NG-R1) Promoted Lymphatic Drainage Function to Ameliorating Rheumatoid Arthritis in TNF-Tg Mice by Suppressing NF-κB Signaling Pathway - Jiao, Danli; Liu, Yang; Hou, Tong; Xu, Hao; Wang, Xiaoyun; Shi, Qi; Wang, Yongjun; Xing, Qiujuan; Liang, Qianqian (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that is primarily characterized by synovial inflammation. Our previous studies demonstrated that the lymphatic system is critical for the development and maintenance of RA disease, and sufficient lymph drainage helps to improve joint inflammation. In this study, we found that NG-R1, the main active component in the traditional Chinese medicinal herb Sanchi, activating lymphatic function can attenuate synovial inflammation. According to histopathological staining of ankle sections, NG-R1significantly decreased the area of inflammation and reduced bone destruction of ankle joints in TNF-Tg mice. Near infrared-indocyanine green (NIR-ICG) lymphatic imaging system has shown that NG-R1significantly improved the lymphatic drainage function. However, the molecular mechanism of its activity is not properly understood. Our in-depth study demonstrates that NG-R1 reduced the inflammatory cytokine production of lymphatic endothelial cells (LECs) stimulated by TNF-α, and the mechanism is ameliorated the phosphorylation of IKKα/β and p65, and the translocation of p65 into the nucleus. In summary, this study proved that NG-R1 promoted lymphatic drainage function to ameliorating rheumatoid arthritis in TNF-Tg mice by suppressing NF-κB signaling pathway.